Pengaruh Citra Destinasi dan Kepercayaan Wisatawan terhadap Keputusan Berkunjung - Raihan Wishal Nafis (Fakultas Ekonomi Universitas Panca Marga, 2020)
This research is quantitative with explanatory and correlations approaches, where this study explains the condition of each variable and explains the effect of destination image variables and tourist’s trust on visit decision variable. The population is domestic tourists who visiting Balekambang Beach Malang on December 2019 or can be said of the study population is infinite population. While the samples used were 100 people from visitors to Balekambang Beach Malang. The number 100 is obtained after the calculation is done using the Lemeshow formula. The method of collecting data using a questionnaire and using the purposive sampling method. Keyword: Decision Visit, Destination Image, Tourists Trust